Elucidating the role of Campylobacter concisus –derived indole metabolites in gut inflammation and immune modulation - Jong-Duk Park; Seoung Rak Lee; Catherine Dhennezel; Noel Taylor; Andrea Dame; Motohiko Kadoki; Gleb Pishchany; Daniel B. Graham; Ramnik J. Xavier; Mohammad R. Seyedsayamdost (Proceedings of the National Academy of Sciences, 2025)
The gut microbiota plays a pivotal role in maintaining human health with dysbiosis linked to a variety of diseases. Metagenome sequencing and robust statistical analysis have linked specific strains, including the gut bacterium Campylobacter concisus , to Crohn’s disease and ulcerative colitis, together known as inflammatory bowel disease (IBD). However, the roles of this and other strains in disease progression remain to be investigated. Herein, we assess the contribution of C. concisus secondary metabolites to inflammation. Through untargeted metabolomics, we identified a diverse array of nineteen indole-containing metabolites produced by C. concisus , including trisindoline, previously isolated from a marine bacterium. Collectively, these metabolites modulate inflammatory responses by significantly inducing the release of proinflammatory cytokines interleukin (IL)-1β, IL-6, IL-8, and MCP-1. The metabolites act through the aromatic hydrocarbon receptor arylhydrocarbon receptor and in vivo intravital imaging revealed a marked increase in the recruitment and activation of immune cells, specifically neutrophils and macrophages, following the administration of trisindoline. Several indole metabolites also exhibited antimicrobial activity against commensal strains that facilitate a proper immune response. Our study provides a possible rationale for the association of C. concisus with IBD and underscores the complex interplay between gut bacteria and host immunity. The identification of indole-derived secondary metabolites as key modulators of inflammation offers new avenues for therapeutic intervention.